Genome size evolution in the beetle genus Diabrotica. Issue 4 (2nd March 2022) - Lata, Dimpal; Coates, Brad S; Walden, Kimberly K O; Robertson, Hugh M; Miller, Nicholas J
Abstract: Diabrocite corn rootworms are one of the most economically significant pests of maize in the United States and Europe and an emerging model for insect–plant interactions. Genome sizes of several species in the genus Diabrotica were estimated using flow cytometry along with that of Acalymma vittatum as an outgroup. Genome sizes ranged between 1.56 and 1.64 gigabase pairs and between 2.26 and 2.59 Gb, respectively, for the Diabrotica subgroups fucata and virgifera; the Acalymma vittatum genome size was around 1.65 Gb. This result indicated that a substantial increase in genome size occurred in the ancestor of the virgifera group. Further analysis of the fucata group and the virgifera group genome sequencing reads indicated that the genome size difference between the Diabrotica subgroups could be attributed to a higher content of transposable elements, mostly miniature inverted-transposable elements and gypsy-like long terminal repeat retroelements.